Effectiveness of Use of UV Lamp in Disinfection of Additioned Vaname Shrimp (Litopenaeus vannamei) Cultivation Media Bacteria Vibrio Harveyi - Hapizah, Imro'atul; Junaidi, Muhammad; Azhar, Fariq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
One of the most promising fisheries products in Indonesia is vaname shrimp (Litopenaeus vannamei), which is also a top export comodity. From year to year the value of shrimp exports and production continues to increase. However, vaname shrimp are susceptible to bacterial and viral attacks, so countermeasures are needed, one of which is by disinfecting the cultivation media using a UV lamp. The aims of this research is to determine the level of effectiveness of UV lamps in disinfection of cultivation media. Experimental methodology with a completely randomized plan (RAL) is the method used in this research, with 4 trials and 3 replications. The results of the research conducted showed that UV lamps were able to reduce the total bacterial count to 4.69 x 108 CFU/mL at UV lamp 41 watt, reduce the total Vibrio bacteria to 30.33 x 106 CFU/mL at UV lamp 41 watt, increase the THC value to 8.83 x 106 CFU/mL cells/ml at P4, hyaline cells range from 31% – 54.67%, granulocyte cell values ​​range from 29.33% – 42%, semigranulocyte cells range from 16% – 27%, the highest AF value at P4 is 32.19%, and the lowest in P1 was 79.69%. Based on the findings, it is possible to conclude that UV lights can be used as a disinfectant of cultivation media, but the right dose or light power is needed to get maximum results.